Talaromycosis from Wuhan: two-case report and literature review - Yao, Zhiyuan; Pan, Zhou; Li, Guang; Liao, Zhaomin; Yu, Zhen; Zhan, Liying; Xia, Wenfang (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Talaromycosis is a serious opportunistic infectious disease caused by Talaromyces marneffei, which mostly occurs in immunocompromised patients. The disease is mainly prevalent in tropical countries and regions of Southeast Asia and South Asia, but non-endemic areas also have Talaromycosis patients. The disease has no characteristic clinical manifestations and is difficult to diagnose. Delayed diagnosis often leads to death. Case presentation: Both patients had cellular immunodeficiency. Case 1 had a history of Acquired immune deficiency syndrome, and case 2 had a history of renal transplantation and glucose-6-phosphate dehydrogenase deficiency. They all had a fever, anemia, fatigue, and skin lesions. Case 1 had gastrointestinal bleeding, enlarged lymph nodes, and hepatosplenomegaly. Case 2 had a cough and dyspnea. Both patients had thrombocytopenia and hypoalbuminemia, an increased neutrophil ratio, procalcitonin, and C-reactive protein, and abnormal liver function and coagulation dysfunction. Case 1 Sputum culture, blood culture, and bronchoalveolar lavage fluid were positive for T. marneffei. T. marneffei was detected in the blood culture of case 2, with infection of Candida parapsilosis and Pneumocystis jirovecii. Chest computed tomography scan mainly showed pulmonary exudative lesions. Although these 2 patients were actively treated, they died of poor efficacy.Talaromycosis has an insidious onset, long course, atypical clinical symptoms, imaging performance and laboratory results, difficult diagnosis, and high mortality. Therefore, it is important to promptly consider and treat Talaromycosis in immunocompromised patients upon infection in order to reduce mortality.